2016
DOI: 10.1038/srep28279
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV microRNA expression in a novel Indian cohort

Abstract: HIV-1 replication inside host cells is known to be regulated by various host factors. Host miRNAs, by virtue of its normal functioning, also regulate HIV-1 RNA expression by either directly targeting virus mRNAs or indirectly by regulating host proteins that HIV-1 uses for own replication. Therefore, it is highly possible that with differential miRNA expression, rate of disease progression will vary in HIV-1 infected individuals. In this study we have compared expression of a panel of 13 reported anti-HIV miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Another interesting deregulated miRNA is miR-155-5p. This miRNA was downregulated in LTNP compared to rapid and typical progressors and is proposed as a critical setting for long-term non-progression [83]. In fact, Witwer et al [63] described a lower amount of miR-155 in PBMCs from healthy donors compared to viremic HIV-infected patients and miR-155 levels from elite controllers in our study are similar to those of healthy donors.…”
Section: Discussionsupporting
confidence: 64%
“…Another interesting deregulated miRNA is miR-155-5p. This miRNA was downregulated in LTNP compared to rapid and typical progressors and is proposed as a critical setting for long-term non-progression [83]. In fact, Witwer et al [63] described a lower amount of miR-155 in PBMCs from healthy donors compared to viremic HIV-infected patients and miR-155 levels from elite controllers in our study are similar to those of healthy donors.…”
Section: Discussionsupporting
confidence: 64%
“…To date, only one article has reported the relationship between miR‐382‐5p and virus replication, that is, the expression of miR‐382 has positively correlated with the viral load of human immunodeficiency virus‐1 (HIV) among long term non‐progressors (LTNPs) . To our knowledge, our study suggested for the first time that miR‐382‐5p could promote the replication of PRRSV.…”
Section: Discussionmentioning
confidence: 72%
“…This observation suggested that specific miRNAs are potential biomarkers for differentiating the stages of progression of HIV-1 infection (Houzet et al, 2008). Dey et al (2016) compared the expression of miRNAs in PBMCs between long-term non-progressors (LTNP), slow progressors, and rapid progressors. Levels of miR-382-5p were lower in LTNP and displayed a positive linear correlation with plasma viral load.…”
Section: Changes In Mirna Levels In Pbmcs and Serum From Patients Basmentioning
confidence: 99%
“…A combination of miR-382-5p and miR-155-5p can be used to distinguish between LTNP and chronic progressors, and between infected and non-infected individuals. Decreases in the levels of miR-382-5p and miR-155-5p are beneficial for the control of disease progression (Dey et al, 2016).…”
Section: Changes In Mirna Levels In Pbmcs and Serum From Patients Basmentioning
confidence: 99%
See 1 more Smart Citation